2018
DOI: 10.1038/s41598-018-34523-3
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal and network alterations in human mucopolysaccharidosis type VII iPSC-derived neurons

Abstract: Mucopolysaccharidosis type VII (MPS VII) is a lysosomal storage disease caused by deficient β-glucuronidase (β-gluc) activity. Significantly reduced β-gluc activity leads to accumulation of glycosaminoglycans (GAGs) in many tissues, including the brain. Numerous combinations of mutations in GUSB (the gene that codes for β-gluc) cause a range of neurological features that make disease prognosis and treatment challenging. Currently, there is little understanding of the molecular basis for MPS VII brain anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…[85] generated 3-dimentional neurospheres from two patient iPSCs cell lines. The MPS VII iPSC-derived neurons displayed the typical features associated with the disease phenotype like deficient β-glucuronidase activity, increased GAG accumulation, ultrastructural aberrations in the lysosome, expanded endocytic compartments, and increased autophagosomes [85]. Ratiometric calcium imaging demonstrated that MPS VII iPSC neurospheroids displayed levels of cytosolic calcium and KCl-induced depolarization similar to those of normal controls, suggesting identical synaptic vesicle trafficking process.…”
Section: Ipscs As An Emerging Model To Study Human Neuronal Dysfunctimentioning
confidence: 87%
See 4 more Smart Citations
“…[85] generated 3-dimentional neurospheres from two patient iPSCs cell lines. The MPS VII iPSC-derived neurons displayed the typical features associated with the disease phenotype like deficient β-glucuronidase activity, increased GAG accumulation, ultrastructural aberrations in the lysosome, expanded endocytic compartments, and increased autophagosomes [85]. Ratiometric calcium imaging demonstrated that MPS VII iPSC neurospheroids displayed levels of cytosolic calcium and KCl-induced depolarization similar to those of normal controls, suggesting identical synaptic vesicle trafficking process.…”
Section: Ipscs As An Emerging Model To Study Human Neuronal Dysfunctimentioning
confidence: 87%
“…Reduced levels of synaptophysin were also reported in the mouse model of MPS IIIB [84], in human iPSC-derived neurons from MPS VII patients [85] and in the occipital and parietal lobes of sheep with NCL (CLN6) [86]. Two different mechanisms have been proposed to explain this reduction.…”
Section: Changes In Synaptic Proteinsmentioning
confidence: 88%
See 3 more Smart Citations